Relational Security - A future in Ageing Research? - Akram, Owasim (Magyar Gerontológia, 2024)
The question of what constitutes a fulfilling late life remains a crucial question in ageing research. Although individual experiences of ageing may vary depending on the context, the overarching factors that influence ageing across cultures are largely determined by the nature of individuals’ relationships with individuals, family, community and institutions.